Chapter 13 - Assessment of Catchment Water Resources Availability Under Projected Climate Change Scenarios and Increased Demand in Central Rift Valley Basin - Gadissa, Takele; Nyadawa, Maurice; Behulu, Fiseha; Mutua, Benedict (ScienceDirect, 2019)
This chapter describes the impact of climate change on available water resources under increasing demand in Central Rift Valley Basin. The study used the ensemble mean of five regional climate models (RCMs) under CORDEX—Africa. Two Representative Concentration Pathways, RCP4.5 and RCP8.5, for current (1985–2016) and scenario period (2041–2070) were considered. The study has revealed that maximum temperature will increase on average by 1.73°C under RCP4.5 to 2.36°C under RCP8.5. Minimum temperature will increase by 2.16°C under RCP4.5 to 3.07°C under RCP8.5. On average, precipitation decreases by 7.97% and − 2.55% under RCP4.5 and RCP8.5, respectively. Moreover, the average streamflow of Meki River will change by − 10.4% and 0.5% under RCP4.5 and RCP8.5, respectively. However, the streamflow of Ketar River will decline by 18.8% and 3.4% on average under RCP4.5 and RCP8.5, respectively. Hence, the available water resources will not meet the projected demand in the scenario period.
Keywords: Climate change; Demand; Stream flow; RCMs; RCP4.5; RCP8.5